Qualitative trial of psoriasis assessment by thermography - Zalewska, Anna; Gralewicz, Grzegorz; Owczarek, Grzegorz; Więcek, Bogusław; Narbutt, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Psoriasis is a common skin disease of a strong genetic component, which affects up to 2% of human population world-wide. The aim of the study was to evaluate in a qualitative way skin lesions in psoriasis vulgaris patients. ThermaCam INFRAMETRICS 290E with a temperature resolution of 0.1 o C used in the study. Twenty patients with both stable and eruptive disease (mainly after upper truct respiratory infection) were included. When evaluating stable lesions, areas of increased temperature were ruthly confined to the visually observed psoriatic skin lesions. However, when eruptive lesions were assessed, areas of increased temperature vastly exceeded clinical borders of the lesions. Based on the obtained results, it could be suggested that thermography may be regarded as a useful method in classifying psoriatic lesions into active and stable and in clinical evaluation of psoriasis vulgaris activity.